Digital Marketing Strategies to Boost Sales: A Case Study of Mama Ai Cake Bukittinggi - Khairani, Nanda; Elmizan, Gina Havieza (Darul Yasin Al Sys, 2025)
This research is motivated by the tight competition in the culinary business in Bukittinggi City, changes in consumer behavior that prioritize online shopping through social media, which is called digital marketing. The purpose of this study is to determine whether the digital marketing strategy carried out by Mama Ai Cake has been implemented properly and what are the obstacles faced by Mama Ai Cake in implementing digital marketing strategies to increase sales. The research method used is qualitative research conducted by interviews, observations and documentation. The informants in this study consisted of key informants, namely the owner of Mama Ai Cake and supporting informants, namely seven Mama Ai Cake consumers. The results of this study indicate that the implementation of a digital marketing strategy using social media by applying the 4P Marketing Mix theory (Product, Price, Place and Promotion) at Mama Ai Cake has not been carried out optimally because there are obstacles that affect the sales volume and income of Mama Ai Cake.